Syntaxin 3 regulates apical membrane integrity in proximal tubule epithelial cells and prevents Fanconi syndrome development: basic research - Okushima, Hiroki; Inoue, Kazunori; Imai, Atsuhiro; Matsumoto, Ayumi; Tamai, Natsune; Kunii, Masataka; Iriuchijima, Nobuhisa; Adam, Rüdiger; Al Rawahi, Yusriya; Al Sinani, Siham; Yamamoto, Takeshi; Mizui, Masayuki; et al. (Kidney international, 2025)
Introduction - Epithelial cell polarity is crucial for the proper functioning of various organs, including the kidneys. Syntaxin 3, a key molecule in membrane-vesicle fusion, is localized in the apical membrane of proximal tubule epithelial cells (PTECs). Although in vitro studies using the other type of epithelial cells besides PTECs have shown the role of syntaxin 3 in regulating apical membrane integrity, its function in epithelial cells in vivo, particularly in PTECs, remains undefined. - Methods - We analyzed the renal phenotypes of a newly generated PTEC-specific Stx3 knockout mice (Stx3-cKO) and examined urine samples from patients with microvillus inclusion disease (MVID) carrying STX3 mutations. - Results - Stx3-cKO mice exhibited features of Fanconi syndrome, including increased urinary excretion of phosphorus, glucose, amino acids, and low-molecular-weight proteins. Patients with MVID showed similar urinary abnormalities. The mice exhibited brush border atrophy and vesicle transport stagnation, as evidenced by electron microscopy, and increased subapical localization of trafficking markers, Rab11 and vesicle-associated membrane protein 8. Key transporters and receptors including sodium-dependent phosphate cotransporter type 2a, sodium-glucose cotransporter 2, a protein related to the neutral and basic amino acid transport protein rBAT, and megalin showed mislocalization and/or altered expression. Syntaxin 3 deficiency disrupted the apical expression of ezrin, a crucial protein that links the actin cytoskeleton to the plasma membrane. Both receptor-mediated and fluid-phase endocytosis were impaired in Stx3-cKO mice. - Conclusions - Our results highlight the critical role of syntaxin 3 in maintaining PTEC function and apical polarity, providing new insights into the kidney manifestations of MVID and the molecular mechanisms underlying Fanconi syndrome.
Online verfügbar: 29. September 2025, Artikelversion: 19. November 2025
Gesehen am 17.02.2026